2017
DOI: 10.3390/resources6040048
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Policy Integration of Sustainable Consumption and Production into National Policies

Abstract: Sustainable Consumption and Production (SCP) was adopted as a stand-alone goal and reflected as one of the cross-cutting objectives of the Sustainable Development Goals (SDGs), with a central role to address global resource consumption and its associated environmental impacts, as well as numerous social and economic issues. With this broad characterization of SCP, policy integration is crucial in addressing it at national level. This paper analyzes characteristics of SCP policy integration based on a survey of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 12 publications
0
12
0
3
Order By: Relevance
“…The identified lifestyle factors were beyond a single product category or domain, as illustrated by a factor referring to car driving, leisure, and product consumption. This cross-cutting nature of lifestyle factors implies the necessity to address consumer lifestyles across different consumption domains, which confirms the importance of policy integrations on sustainable consumption and production between different policy sectors [52].…”
Section: The Lifestyle Factors Contributing To Carbon Footprints In Vmentioning
confidence: 80%
“…The identified lifestyle factors were beyond a single product category or domain, as illustrated by a factor referring to car driving, leisure, and product consumption. This cross-cutting nature of lifestyle factors implies the necessity to address consumer lifestyles across different consumption domains, which confirms the importance of policy integrations on sustainable consumption and production between different policy sectors [52].…”
Section: The Lifestyle Factors Contributing To Carbon Footprints In Vmentioning
confidence: 80%
“…Yet these broader assessments of behavioural change often neglect strategies to affect the supply chain and do not yet consider the life-cycle greenhouse gas emissions (a.k.a. carbon footprints) that more narrow studies of specific strategies have shown to be important (Chester, Pincetl, Elizabeth, Eisenstein, & Matute, 2013;Hellweg & MilĂ  i Canals, 2014;Hoekstra & Wiedmann, 2014;Koide & Akenji, 2017;O'Rourke, 2014;Scholz, Eriksson, & Strid, 2015) But increasing attention is being given to potential behavioural changes at points along the emitter-to-final-consumer supply chain aside from the primary emitter (Creutzig et al, 2018;Steininger et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of policy integration is an important starting point for transitioning consumption and production systems (Koide and Akenji 2017). Reflexive, distributed, and multi-scalar approaches demand a degree of direction and consistency across organizational, sectoral, and institutional boundaries.…”
Section: Resultsmentioning
confidence: 99%